Signaling and operating system support for native-mode ATM applications. - Sharma, R. (Computer communication review.)
Applications communicating over connectionless networks, such as IP, cannot obtain per-connection Quality of Service (QoS) guarantees. In contrast, the connection-oriented nature of the ATM layer and its per-virtual-circuit QoS guarantees are visible to a native-mode ATM application. We describe the design and implementation of operating system and signaling support for native-mode applications, independent of the semantics of the protocol layers or of the signaling protocol. The work was done in the context of a Unix-like operating system and the Xunet 2 wide-area high-speed ATM network. The IPC-based interface between an application and the signaling entity allows processes to request parameterized virtual circuits, and the signaling-kernel interface allows resources to be reclaimed from prematurely terminating processes. We also built a simple encapsulation layer over raw IP that allows any host with IP access to send AAL frames into the wide-area network with little performance degradation. Our design makes it simple to port existing TCP/IP socket applications to a native-mode ATM protocol stack and also enables interoperation of existing IP networks with our ATM network. Our experience has been positive - the design is robust, easily extendible and scales well with the number of open connections.